Indicadores biológicos ou ambientais, qual reflete melhor a qualidade de estuários tropicais? - Francisco, Milena Maria de Luna (2019)
Due to the ability to reflect changes in the aquatic ecosystem, benthic macroinvertebrate communities have been used on a wide scale in surveys worldwide. The objective of this work was to evaluate which of the following indicators: biological through the Shannon-Wiener diversity index and thermodynamic indexes such as ecoregeneration and specific eco-exergy or environmental ones through the TRIX trophic index index, are able to reflect better the water quality of estuaries in the tropical region. The hypothesis tested is that the biological aspects are the ones that best reflect the state of the water quality because they are formed by a very diversified group, with different levels of tolerance and the genetic information incorporated in their biomass, able to reflect changes in the environment in temporal and spatial scale. The study was carried out in two tropical estuaries located in the state of Paraíba, Brazil, the Mamanguape River estuary and the Paraíba do Norte River estuary, both with different uses and occupations of the soil. The estuaries were divided into 4 zones with three points, each containing three sample replicates. To evaluate if there were significant differences between the zones, periods and estuaries for the determined indicators, a PERMANOVA was performed. However, when evaluating the community of macrobenthic, it was possible to perceive that this increase of eco-exergy is due to the presence in high amount of the exotic mollusk Bracdontes, increasing biomass and consequently the index, thus showing the importance of the study of community composition. The specific eco-exergy reflected as expected, presenting lower values in more disturbed places. The places where the highest values were obtained for the Shannon were observed the presence of tolerant species in the majority, thus justifying the high values of the index in places of impact. The TRIX was higher in the estuary of the Paraíba River, due to the greater impact due to the anthropic activities suffered in this, however, did not differentiate as expected from the Mamanguape River estuary considering that it has lower anthropic activity. Thus, it was concluded that the biological indicators together reflect better the environmental quality and that the environmental indicator can be used in a complementary way and not in a unique way.